Muscle damage produced during a simulated badminton match in competitive male players - Abian, P.; Del Coso, J.; Salinero, J. S.; Gallo-Salazar, C.; Areces, F.; Ruiz-Vicente, D.; Lara, B.; Soriano, L.; Munoz, V.; Lorenzo-Capella, I.; Abian-Vicen, J. (Research in Sports Medicine, 2015)
The purpose of the study was to assess the occurrence of muscle damage after a simulated badminton match and its influence on physical and haematological parameters. Sixteen competitive male badminton players participated in the study. Before and just after a 45-min simulated badminton match, maximal isometric force and badminton-specific running/movement velocity were measured to assess muscle fatigue. Blood samples were also obtained before and after the match. The badminton match did not affect maximal isometric force or badminton-specific velocity. Blood volume and plasma volume were significantly reduced during the match and consequently haematite, leucocyte, and platelet counts significantly increased. Blood myoglobin and creatine kinase concentrations increased from 26.5 ± 11.6 to 197.3 ± 70.2 µg·L-1 and from 258.6 ± 192.2 to 466.0 ± 296.5 U·L-1, respectively. In conclusion, a simulated badminton match modified haematological parameters of whole blood and serum blood that indicate the occurrence of muscle fibre damage. However, the level of muscle damage did not produce decreased muscle performance.